Hubungan Academic Stress dengan Problematic Internet Use pada Mahasiswa Pengguna Social Media di Universitas Islam Bandung - Amelia Nisa Aqila; Lilim Halimah (Bandung Conference Series: Psychology Science, 2023)
Abstract. The improper utilization of the internet can lead to the occurrence of Problematic Internet Use among students. As students rely on the internet for their learning process, they are also susceptible to the risks of Problematic Internet Use. Excessive usage can disrupt study time, diminish productivity levels, and disturb the balance between academic and social life, resulting in Academic Stress. This research aims to examine the correlation between Academic Stress and Problematic Internet Use among students who utilize social media at the Islamic University of Bandung. The study was conducted on 429 students, aged between 18-24 years, who access the internet for more than 5 hours daily, outside of academic or professional purposes, consequently experiencing physical and psychological issues due to internet usage. The data was collected using an adapted questionnaire from the Student-Life Stress Inventory and the Generalized Problematic Internet Use Scale 2 (GPIUS-2). Data analysis was performed using the Pearson Product Moment correlation test with the assistance of IBM SPSS 26 software for Windows. The results of the data analysis indicate a correlation coefficient value of r=0.795 with a significance level of P=0.000<0.05, its mean there is significantly a strong positive relationship between Academic Stress and Problematic Internet Use among students who utilize social media at the Islamic University of Bandung. Abstrak. Penggunaan internet yang tidak tepat dapat mengakibatkan Problematic Internet Use Mahasiswa. Mahasiswa sebagai pengguna internet untuk proses pembelajaran pun berisiko terhadap Problematic Internet Use. Penggunaan yang berlebihan dapat mengganggu waktu belajar, mengurangi tingkat produktivitas, dan mengubah keseimbangan antara kehidupan akademik dan sosial yang berdampak pada Academic Stress. Penelitian ini bertujuan untuk mengetahui hubungan antara Academic Stress dengan Problematic Internet Use pada mahasiswa pengguna social media di Universitas Islam Bandung. Penelitian dilakukan kepada 429 mahasiswa di Universitas Islam Bandung dengan rentang usia 18-24 tahun dan mengakses internet lebih dari 5 jam per hari diluar kepentingan akademik atau professional sehingga mengalami masalah fisik maupun psikologis akibat penggunaan internet. Alat pengumpul data berupa kuesioner adaptasi Student-Life Stress Inventory dan Generalized Problematic Internet Use Scale 2 (GPIUS2). Analisis data menggunakan uji teknik korelasi Pearson Product Moment dengan alat bantu software IBM SPSS 26 for windows. Hasil analisis data menunjukkan nilai koefisien korelasi sebesar r=0.795 dengan nilai P=0.000<0.05 artinya secara signifikan terdapat hubungan positif dengan kategori yang kuat antara Academic Stress dan Problematic Internet Use pada Mahasiswa pengguna social media di Universitas Islam Bandung.